Development of an intelligent solar energy system for off-grid application - Ng, Cindy Shi Hui. (2010)
Renewable energy has been a research area of exponentially increasing interest since the past decade along with the more attention that people pay to environment and energy problems. The growing demand for clean sources of energy has expanded dramatically in recent years as conventional energy like oil becomes scarce and more expensive. Because of this growth, it has led to demand for searching alternative source energy. Therefore, the aim of this project is to build a solar energy system in an isolated home. This project focuses on two parts. It started on design and development of the inverter system. The inverter system consists a basic DC-DC boost converter topology to boost the DC voltage from the charge controller to a higher voltage level for the DC-AC inverter and the single-phase full bridge inverter to converter the DC voltage to an AC voltage of 230Vac at 50Hz. The second parts followed by studying the photovoltaic (PV) module to find its characteristics and maximum power point (MPP) under various solar radiations. Controller circuitry to track the maximum power point was introduced. Simulations were carried out using PSIM software for verification before hardware circuits were developed for actual implementation.